PENDUGAAN CADANGAN BIOMASSA DI ATAS PERMUKAAN TANAH PERKEBUNAN KELAPA SAWIT DI SUMATERA UTARA - Muhdi, Muhdi; Risnasari, Iwan; Bayu, Eva Sartini (Bumi Lestari Journal of Environment; Vol 15 No 1 (2015))
The objective of the research was to find the model of above ground biomass in the oil palm plantation, North Sumatera. The research was done at the oil palm plantation, North Sumatera. The effect of oil palm plantation to biomass stock in the plots were studied by using the data of three plots with each size 100 m x 100 m. The plots are placed based on purposive sampling. Above ground biomass stocks are counted by allometric equation. The results of the research showed that allometric equation of oil palm trees was W = 0,003 D . The result  showed that above ground biomass of oil palm plantation in the North Sumatera were 64.20 Mg ha
Keywords: above ground, biomass, oil palm, plantation, model